Evaluation of a typhoid/paratyphoid diagnostic assay (TPTest) detecting anti-Salmonella IgA in secretions of peripheral blood lymphocytes in patients in Dhaka, Bangladesh. - Farhana Khanam; Alaullah Sheikh; Md Abu Sayeed; Md Saruar Bhuiyan; Feroza Kaneez Choudhury; Umme Salma; Shahnaz Pervin; Tania Sultana; Dilruba Ahmed; Doli Goswami; Md Lokman Hossain; K Z Mamun; et al. (Public Library of Science (PLoS), 2013)
Rapid and reliable diagnostic assays for enteric (typhoid and paratyphoid) fever are urgently needed. We report the characterization of novel approach utilizing lymphocyte secretions, for diagnosing patients with enteric fever by the TPTest procedure.TPTest detects Salmonella-specific IgA responses in lymphocyte culture supernatant. We utilized TPTest in patients with suspected enteric fever, patients with other illnesses, and healthy controls. We also evaluated simplified modifications of TPTest for adaptation in laboratories with limited facilities and equipment.TPTest was positive in 39 (27 typhoid and 12 paratyphoid A) patients confirmed by blood culture and was negative in 74 healthy individuals. Among 32 individuals with other illnesses, 29 were negative by TPTest. Of 204 individuals with suspected enteric fever who were negative by blood culture, 44 were positive by TPTest and the patients were clinically indistinguishable from patients with confirmed bacteremia, except they were more likely to be under 5 years of age. We evaluated simplifications in TPTest, including showing that lymphocytes could be recovered using lysis buffer or buffy coat method as opposed to centrifugation, that incubation of cells at 37°C did not require supplemental CO2, and that results were available for majority of samples within 24 hours. Positive results by TPTest are transient and revert to negative during convalescence, supporting use of the test in endemic areas. The results can also be read using immunodot blot approach as opposed to ELISA. Since no true gold standard currently exists, we used a number of definitions of true positives and negatives. TPTest had sensitivity of 100% compared to blood culture, and specificity that ranged from 78-97% (73-100, 95% CI), depending on definition of true negative.The TPTest is useful for identification of patients with enteric fever in an endemic area, and additional development of simplified TPTest is warranted.